(3GdEYdGf aj GdCfXeI GdEPGYjI GdeYGUQI (B/s - (3eUWai, ghjOGs ((3GdbGgQI(B: s (3GdOGQ GdeUQjI GddHfGfjI(B, s, 1999)
(3GdeJZjQGJ GdeMOOI dSeGJ GdEYdGf aj GdCfXeI GdEPGYjI GdeYGUQI,GdEYdGf aj GdfXGe GdEPGYj GdJLGQj,GdEYdGf aj GdfXGe GdEPGYj GdMchej hGdeNJdW,GdEYdGf aj GdCfXeI GdEPGYjI ddOhd GdfGejI,GdJTQjYGJ h GdVhGHW GdEYdGfjI aj GdfXGe GdJLGQj hGdfXGe GdMchej,GdEYdGf aj GdfXGe GdEPGYj GdeUQj(B:(3QGOjh h JdjaRjhf,ebGQfI Hjf GdeeGQSI GdEYdGfjI hGdCgOGa GdbhejI,fJGFL GdOQGSI GdJMdjdjI dYjfI ef EYdGfGJ EPGYI GdTQb GdChSWs
(3HHdjhZQGajG(B:273-278s
Keywords: (3GdEYdGfs; (3eUQs